2020
DOI: 10.5382/econgeo.4746
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Permian-Triassic Ore-Bearing Intrusions of the Norilsk Region with the Volcanic Sequence of the Siberian Traps Based on the Paleomagnetic Data

Abstract: We present detailed paleomagnetic data from the Permian-Triassic Cu-Ni-Pt–bearing intrusions of the Norilsk region (northwestern Siberian platform). Based on the analysis of geomagnetic secular variations recorded in the intrusions, we correlate the Norilsk ore-bearing intrusions with the Siberian Traps volcanic sequences in the region. The similarity of paleomagnetic directions of the ore-bearing intrusions to those of the Morongovsky and Mokulaevsky volcanic formations suggests that the emplacement of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 47 publications
1
17
0
2
Order By: Relevance
“…Among the differentiated mafic‐ultramafic bodies, only three specific intrusions (Norilsk‐1, Talnakh, and Kharaelakh) contain economic mineralization, featuring a combination of exceptionally thick ore bodies within relatively thin subhorizontal and internally zoned doleritic units (Figures 2a and 2b), and these are classified as Norilsk‐type (Sluzhenikin et al., 2014; Zen’ko & Czamanske, 1994). These ore‐bearing intrusions have been correlated on the basis of geochemistry, U‐Pb geochronology, and paleomagnetic records with a marked change in magma source and eruptive style along with greatly increased rate of magma production marking the transition from the Middle series which terminates above the uppermost Nd , in a transitional series that includes the lowermost Morongovsky ( Mr ) lavas, to the much more voluminous Upper series which comprise the remainder of the Mr and the Mokulaevsky ( Mk )‐Samoedsky ( Sm ) lava series (Latyshev et al., 2020; Pavlov et al., 2019).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the differentiated mafic‐ultramafic bodies, only three specific intrusions (Norilsk‐1, Talnakh, and Kharaelakh) contain economic mineralization, featuring a combination of exceptionally thick ore bodies within relatively thin subhorizontal and internally zoned doleritic units (Figures 2a and 2b), and these are classified as Norilsk‐type (Sluzhenikin et al., 2014; Zen’ko & Czamanske, 1994). These ore‐bearing intrusions have been correlated on the basis of geochemistry, U‐Pb geochronology, and paleomagnetic records with a marked change in magma source and eruptive style along with greatly increased rate of magma production marking the transition from the Middle series which terminates above the uppermost Nd , in a transitional series that includes the lowermost Morongovsky ( Mr ) lavas, to the much more voluminous Upper series which comprise the remainder of the Mr and the Mokulaevsky ( Mk )‐Samoedsky ( Sm ) lava series (Latyshev et al., 2020; Pavlov et al., 2019).…”
Section: Overviewmentioning
confidence: 99%
“…Based on their geochemical similarity, we adopt the average composition of coeval Mr-Mk basalts (Table S1) as a likely reference point to model magma evolution for these intrusions, which receives additional support from the matching paleomagnetic directions of Norilsk-type intrusions YAO AND MUNGALL 10.1029/2020JB020823 8 of 22 and lavas at Mr-Mk formations (Latyshev et al, 2020;Pavlov et al, 2019). This parental magma is suggested to have contained ∼0.6% H 2 O based upon analyses of melt inclusions in primitive olivine, and crystallization is assumed to occur around ∼0.5 kbar and △QFM-1 during emplacement (Krivolutskaya, 2016).…”
Section: Magmatism During Emplacement Of Norilsk-type Intrusionsmentioning
confidence: 99%
“…Its age of 251.71 ± 0.31 Ma (2σ external error including 238 U decay constant) was determined using chemical abrasion isotope dilution thermal ionization mass-spectrometry (CA-ID-TIMS) on zircon [27]. According to paleomagnetic data, the Kharaelakh intrusion is slightly older than other ore-bearing intrusions in the Norilsk-Talnakh ore district [28], though the difference in age is too small to be resolved by U-Pb data [27]. The rocks of the Kharaelakh intrusion occur within Devonian sediments, which are represented by terrigenous, carbonate and evaporite sediments.…”
Section: Geology Of the Oktyabrsk Depositmentioning
confidence: 99%
“…Steens Basalt plagioclase phenocrysts also contains native Cu (Oregon Sunstones) whereas the Keweenaw deposits are not derived from a magmatic plume but are probably either due to metamorphism or meteoric waters (Brown 2006). Pavlov et al (2019) concluded that, like the CRBG, the Siberian Traps were emplaced rapidly and Latyshev et al (2020) showed that all main ore-bearing intrusions of the Noril'sk Complex, as well as weakly mineralized and barren intrusions, are coeval with the Morongovsky-Mokulaevsky level of the volcanic sequence. However, models for the Noril'sk deposits range from magmas that fed the deposits also feeding lava flows (e.g.…”
mentioning
confidence: 99%